2017
DOI: 10.2500/ajra.2017.31.4385
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Need for Endoscopic Sinus Surgery in Adult Patients with Cystic Fibrosis

Abstract: The occurrence of ESS in adult patients with CF was predicted by previous ESS intervention as well as the severity of CFTR mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, recurrences seem to be inevitable in these patients, especially in those with severe mutations in the CFTR gene [ 7 ]. Individuals with severe CFTR mutations are definitely more likely to undergo ESS than those with mild CFTR mutations [ 66 ].…”
Section: Therapeutic Options For Cf-related Crsmentioning
confidence: 99%
“…Therefore, recurrences seem to be inevitable in these patients, especially in those with severe mutations in the CFTR gene [ 7 ]. Individuals with severe CFTR mutations are definitely more likely to undergo ESS than those with mild CFTR mutations [ 66 ].…”
Section: Therapeutic Options For Cf-related Crsmentioning
confidence: 99%
“…Despite appropriate medical therapy, 20 to 60% of CF patients go on to require ESS [2]. In a retrospective review, Brook et al showed that prior history of ESS and severe CFTR mutations are predictive of ESS while Sinonasal Outcome Test (SNOT)-22 score was not [14]. In a different study, CF patients with nasal polyposis, prior history of ESS, lower forced expiratory volume in one second (FEV1), higher Lund-Mackay score, and higher SNOT-22 score was more likely to elect up-front ESS versus medical therapy.…”
Section: Surgical Managementmentioning
confidence: 99%
“…In an analysis of 91 patients over the age of 16 years who had sinus CT scans, the SNOT‐22 revealed few symptoms, suggesting under‐reporting of symptoms by patients with CF . A retrospective review of adults who were referred to an otolaryngology clinic showed that predictors of future endoscopic sinus surgery (ESS) included previous ESS and severe CFTR mutations; however, the SNOT‐22 was not found to be predictive …”
Section: Extrapulmonary Complicationsmentioning
confidence: 99%